Effect of Alkyl Substituents on the Hydrogen Catalytic Osmylation of Cis and Trans 2-Cyclohexene-Cyclohexanol - Mohammad Raouf Darvich; Jamshid Mohammadi Rovshandeh (Iranian Journal of Chemistry & Chemical Engineering, 1995)
Catalytic osmylation of cis and trans 2-cyclohexene-cyclohexanol (1a) and (1b) are carried out in the presence of N-methyl morpholine-N-oxide. Under the same conditions, only the cis isomer reacted, leading to triol (3). The steric hindrance of the equatorial OH group probably prevents the trans isomer from entering into such reaction. Triol (3) was also obtained from the reduction of the diol-ketone (4).